The Effectiveness of Court-Annexed Mediation in Divorce Disputes: Evidence from Indonesian Religious Courts - Atrizal; Susi Kusmawaningsih; Diana Sari (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study examines the effectiveness of court-annexed mediation in resolving divorce disputes in Indonesian Religious Courts. Mediation has been institutionalized through Supreme Court Regulation No. 1 of 2016 as a mandatory stage in civil litigation, including family law disputes. Using a qualitative socio-legal approach, this research analyzes the legal framework of mediation and its implementation in divorce cases. The findings show that mediation provides an important forum for dialogue between spouses and may lead to reconciliation or negotiated agreements concerning post-divorce issues such as child custody and financial obligations. However, its effectiveness is influenced by several factors, including the willingness of the parties to negotiate, the level of marital conflict, and the competence of mediators. Strengthening mediator capacity and encouraging meaningful participation are essential to improve mediation outcomes.